Application of thermally activated municipal solid waste incineration (MSWI) bottom ash fines as binder substitute. (July 2016) - Tang, P.; Florea, M.V.A.; Spiesz, P.; Brouwers, H.J.H.
Abstract: Untreated municipal solid waste incineration (MSWI) bottom ash fines (0–2 mm) have poor pozzolanic properties, and contain substances which can pose an environmental risk (e.g. heavy metals and salts). This study investigates combined treatments applied on bottom ash fines (BAF) to increase their reactivity. The treated BAF is compared with both untreated BAF and cement, and its contribution to cement hydration is investigated. Additionally, the utilization of the treated BAF in mortar as cement replacement is tested. Finally, the leaching properties of mortars containing treated and untreated BAF are estimated. According to the results obtained, the 28-day compressive and flexural strengths of mortar with 30% treated bottom ash are about 16% and 6% lower than the reference mortar, respectively. The leaching of contaminants from the crushed mortars with BAF are well under the limit values imposed by Dutch legislation.